Who Is More Mobile in Response to Local Demand Shifts in China? - Dongdong Luo; Chunbing Xing (Institute for the Study of Labor (IZA), 2015)
In this paper, we use two nationally representative datasets to examine the population adjustment of demographic groups in response to regional demand shifts between 2000 and 2005. Results from OLS regressions show that population changes of less educated groups are more associated with changes in total city working hours than population changes of educated groups. These findings explain increases in skill premia in coastal regions after China's entry into the WTO, but it does not mean that the former groups are more responsive to demand shocks, because changes in city working hours also reflect other forces such as supply shocks. Using an IV strategy, we find that educated workers are more responsive to demand shocks than those who are less educated. In addition, old subgroups are particularly inert in responding to demand shocks. Our results also suggest that China's household registration (Hukou) system prevents the mobility of urban residents more than it prevents the mobility of rural residents. We propose that Hukou reform should not only abolish the agricultural vs. non-agricultural division, but also change the decentralized (local vs. non-local) feature of the system.
Keywords: J23; R23; 330; local demand shift; population adjustment; Hukou